PENGARUH PENGETAHUAN TEKNOLOGI INFORMASI DAN PENGETAHUAN MANAJEMEN TERHADAP EFEKTIVITAS KERJA KEPALA SEKOLAH MENENGAH ATAS KABUPATEN ROKAN HILIR (Proceeding 7th International Seminar on Regional Education, 2015)
AbstractThis study only measured the aspects of knowledge of information technology and knowledge management on the effectiveness of the head of a high schools in Kabupaten Rokan Hilir. This study uses of quantitative approach, the reseach data obtained from school principels direcly by using taste for variable information technology and knowledge management while the variable effectiveness date collection was obstained by using a questionaire. From the results of hypothesis testing variables and variable information technology knowledge management knowledge to the effectiveness of the principal of all the regression coefficient Î² is positive . This suggests improved independent variables and affect the increase in the dependent variable ( Work Effectiveness principal) , so that the figures obtained : 1 ) Constant value = 45 671 shows a positive value means that when X.1 and X.2 enhanced the effectiveness of the principal increases , 2 ) value b1 = 1,034 indicates a positive value means that when X.1 increased by 1,034 , the effectiveness decreases , 3 ) value b2 = 1,084 is positive , meaning that if X.2 improved sebesra 1084 , then the effectiveness of the principal increases. Results of the study revealed several finding that 1) there is significant influence between technological knowledge information principels of the effectiveness of the principal, 2) there is significant influence between knowledge management principals, 3) both variables greatly affact the effectiviness of the work head schoolKeywords : Knowledge, effectiveness, management of information technology